Influence Speed High-Speed Steel Chisel Cut Against Integrity Carbon Steel Surface - Sumantri, Ricky; Nasution, M. Zakaria Alhafiz (International Journal of Mechanical Computational and Manufacturing Research, 2024)
This research aims to investigate the Influence of High-Speed Steel Cutting Tool Speed on the Surface Integrity of Low Carbon Steel. Low carbon steel is a commonly used material in the industry due to its strength and corrosion resistance. However, the steel processing processes diminish its quality and service life. In this study, variations in high-speed steel cutting tool speeds were used to examine their influence on the surface integrity of low carbon steel. The research results indicate that the cutting speed of high-speed steel tools has a significant impact on the surface integrity of low carbon steel. It was found that increasing the cutting speed can reduce surface damage and make the surface smoother, thereby improving the quality and service life of low carbon steel. However, excessively high cutting speeds can also lead to overheating and excessive wear. Additionally, other factors such as cutting fineness and tool conditions need to be considered in maintaining the surface integrity of low carbon steel. This research provides a better understanding of the relationship between high-speed steel cutting tool speed and the surface integrity of low carbon steel, which can be used as a guideline in the low carbon steel processing to optimize quality and efficiency.